Green Innovation: Harmonizing Creative Art Literacy and Upcycling for Sustainable Community Development: Green Innovation: Harmonizing Creative Art Literacy and Upcycling for Sustainable Community Development - Liena Prajogi; Yulita Fairina Susanti; Wiwiek Mardawiyah Daryanto (Journal of Sustainable Community Development (JSCD), 2026)
The global environmental crisis, marked by escalating plastic waste and climate instability, demands a transition from linear consumption to a restorative circular economy. This paper analyzes the "Green Innovation: Literasi Creative Art" program—a collaborative community development initiative led by MNC University and IPMI Institute. By integrating the "Sustainability Mindset" framework with practical upcycling literacy, the project transformed household waste into high-value creative products. This research employs a participatory workshop methodology to bridge the gap between environmental awareness and actionable "Green Behavior." Findings indicate that creative art serves as a powerful mediator for Sustainable Development Goals (SDG) 12 (Responsible Consumption) and SDG 8 (Decent Work and Economic Growth). The study concludes that fostering a Sustainability Mindset through tactile creative literacy is essential for empowering Micro, Small, and Medium Enterprises (MSMEs) and ensuring long-term ecological stewardship.